Eksistensi Bahasa Indonesia di Lingkungan Masyarakat dan Pendidikan - Wahyu Santoso (Peneliti.net, 2023)
Aim of this research vis to produce inspect about Indonesian language existence, nation character, Indonesian language and English language acts, and Indonesian language using on education domain. Method that used vis bibliography qualitative descriptive methods. Result that acquisition of this research is preservation of Indonesian language so that exist persistent. Character strengthening base is give priority to Indonesian language better than English language. The commoning process of Indonesian language amongst the community can be done by the exercise of speeching skills.Coclusion of this research is language existente supported by education with stron discipline attitude can defend Indonesian language existence from globalisation flow.